Hypnosis as an approach to control pain and anxiety in knee pain: A multiple case report (Research, Society and Development, 2024)
This scientific study explores the efficacy of hypnosis as a therapeutic intervention for managing both pain and anxiety associated with knee pain. The research adopts a multiple case study design, investigating the experiences of individuals suffering from knee pain who underwent hypnosis sessions. The study aims to assess the impact of hypnosis on pain perception, anxiety levels, and overall quality of life in a diverse sample of participants. Methodological rigor is maintained through the use of standardized pain and anxiety assessment tools, longitudinal data collection, and qualitative interviews. Preliminary findings indicate a promising reduction in both pain and anxiety, suggesting the potential of hypnosis as a complementary approach in the multidimensional management of knee pain. The implications of these results for clinical practice and future research avenues are discussed, emphasizing the need for further exploration of hypnosis as a viable therapeutic option in pain and anxiety management.